THE INFLUENCE OF STORE ATMOSPHERE AND CUSTOMER EXPERIENCE ON PURCHASING DECISIONS THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Agustin, Defitri Karunia; Badi’ah, Roudlotul (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Using customer satisfaction as a mediating variable, this study examines how store environment and customer experience influence purchasing decisions at Kae Kopi, Lamongan. With 100 respondents selected using purposeful sampling using the Lemeshow algorithm, this study uses a quantitative methodology. Likert scales were used in the online survey to collect data, and SmartPLS assisted in the partial least squares (PLS) analysis. The findings of the study indicate that, through customer experience satisfaction, retail atmosphere and customer experience have a significant positive impact on purchasing decisions. Compared to the retail environment, customer experience has the greatest impact on customer satisfaction. This study only looks at one object of study and ignores other factors such as brand image and price. To provide more comprehensive insights, further research is recommended to examine more variables and broader items. Keywords: Store Atmosphere; Customer Experience; Customer Satisfaction; Purchasing Decisions